2017
DOI: 10.1515/ijamh-2017-0117
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional comparison of age-related changes in the quadriceps femoris in Japanese basketball players

Abstract: Background This study examines age-related changes in the quadriceps femoris (QF), subdivided into the vastus medialis oblique (VMO), vastus medialis (VM), rectus femoris (RF), vastus intermedius (VI) and vastus lateralis (VL) in basketball players. Subjects Seventy male basketball players were divided into four groups according to age (12-13, 14-15, 16-17, and 18-20 years). Methods Ultrasonography was used to measure muscle architecture of the VMO, VM, RF, VI and VL. We created cubic approximate expressions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
2
8
0
3
Order By: Relevance
“…Although the lack of a signi cant interaction for RF-MT prevented us from identifying speci c between agecategory differences, our results agree with those by Sekine et al 19 , who examined age-related changes in the quadriceps femoris in 70 male basketball players using US. These authors reported that the RF-MT was larger in 16-17-year-olds than those aged 12-13 or 14-15 years, and stated that marked RF growth is expected starting at age 16 years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the lack of a signi cant interaction for RF-MT prevented us from identifying speci c between agecategory differences, our results agree with those by Sekine et al 19 , who examined age-related changes in the quadriceps femoris in 70 male basketball players using US. These authors reported that the RF-MT was larger in 16-17-year-olds than those aged 12-13 or 14-15 years, and stated that marked RF growth is expected starting at age 16 years.…”
Section: Discussionsupporting
confidence: 90%
“…[16][17][18] Speci cally, muscle strength and power generated by muscles in the lower extremities (e.g., the gastrocnemius medialis [GM] and rectus femoris [RF]) are essential in elite basketball performance, regardless of age or gender. 19 Similarly, body fat (i.e., subcutaneous fat thickness [SFT]) has been shown to be speci cally related with performance in basketball. 20 Therefore, accurate means of assessing these physiological indicators are also required for this sport.…”
Section: Introductionmentioning
confidence: 99%
“…Many activities in basketball are considered anaerobic because they are performed at maximal or submaximal intensities. Conversely, activities like sprinting and jumping are interspersed with periods of slow running, walking, or resting during the game-stops, which suggests that the game is similar to high-intensity interval training (HIIT) ( Sekine et al, 2019 ). HIIT is a very effective and time-efficient way to improve AF levels in adults ( Gist et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Specifically, muscle strength and power generated by muscles in the lower extremities (e.g., the gastrocnemius medialis [GM] and rectus femoris [RF]) are essential in elite basketball performance, regardless of age or gender. [19] Similarly, body fat (i.e., subcutaneous fat thickness [SFT]) has been shown to be specifically 2…”
Section: Introductionmentioning
confidence: 99%
“…Muscle architecture largely determines muscle strength and power production, which are both necessary components in optimal athletic performance [16][17][18]. Specifically, muscle strength and power generated by muscles in the lower extremities (e. g., the gastrocnemius medialis [GM] and rectus femoris [RF]) are essential in elite basketball performance, regardless of age or gender [19]. Similarly, body fat (i. e., subcutaneous fat thickness [SFT]) has been shown to be specifically related with performance in basketball [20]; García-Gil et al found positive correlations between the sum of 8 skinfolds (biceps, triceps, subscapularis, abdominal, suprailiac, iliocostal, thigh, and lower leg) and the time in the 20-m sprint test (r = .333) and time in a dribbling test (r = .323), and negative correlations between the sum of skinfolds and height in a CMJ-S test (r = − .318).…”
Section: Introductionmentioning
confidence: 99%